Reproductive cycle progression arrest and modification of cell morphology (shape and biovolume) in the alga Pseudokirchneriella subcapitata exposed to metolachlor - Machado, Manuela Dias (2020)
Metolachlor (MET) is an herbicide widely used and frequently found (at μg L-1) in aquatic systems. This work aimed to study the modes of action of MET on the green microalga Pseudokirchneriella subcapitata. Algae exposed to 115 or 235 μg L-1 MET, for 48 or 72 h, presented a reduction of metabolic activity, chlorophyll a and b content and photosynthetic efficiency. The exposure to 115 or 235 μg L-1 MET also induced growth yield reduction, mean cell biovolume increase and alteration of the typical algae shape (cells lunate or helically twisted) to "French croissant"-type; at these MET concentrations, algal population was mainly composed by multinucleated cells (≥ 4 nuclei), which suggest that MET impairs the normal progression of the reproductive cycle but did not hinder nuclear division. The accumulation of multinucleated cells seems to be the consequence of the incapacity of the parent cell to release the autospores. In conclusion, MET disrupts the physiology of P. subcapitata cells; the disturbance of the progression of the reproductive cycle should be in the origin of growth slowdown (or even its arrest), increase of mean cell biovolume and modification of algal shape. This work contributed to elucidate, in a systematically and integrated way, the toxic mechanism of MET on the non-target organism, the alga P. subcapitata.